The Life of John Ruskin, Volume 1, 1819–1860 - Cook, Edward Tyas (Cambridge University Press, 1911)
In 1911, the New York Times alerted its readers to the forthcoming 'authoritative' biography of Ruskin with the words 'out of a life's devotion to Ruskin and the Herculean task of editing the definitive Ruskin, Mr E. T. Cook is to give us a definitive Ruskin biography also. It will have the authority of a brilliant Oxford scholar, combined with the charm and lightness of a style which makes Mr Cook one of the first of English journalists'. Cook had been given complete access to Ruskin's diaries, notebooks and letters by his literary executors, and Ruskin's family and friends co-operated fully with him. His depth of knowledge of, and sympathy for, his subject make Cook's biography a vital tool for anyone wishing to understand Ruskin's extraordinary achievements in so many fields. Volume 1 covers the period to 1860, the year in which the final volume of Modern Painters was published
Title from publisher's bibliographic system (viewed on 05 Oct 2015)